2012
DOI: 10.1128/jvi.01607-12
|View full text |Cite
|
Sign up to set email alerts
|

Modification of One Epitope-Flanking Amino Acid Allows for the Induction of Friend Retrovirus-Specific CD8+T Cells by Adenovirus-Based Immunization

Abstract: While Friend retrovirus-infected mice readily mount a vigorous CD8؉ T cell response to the leader-gag-derived peptide GagL 85-93 , no GagL 85-93 -specific T cells were detectable in mice immunized against Friend virus (FV) with viral vectors or DNA vaccines. By exchanging one epitope-flanking amino acid or using a scaffold protein we were able to demonstrate for the first time the induction of GagL 85-93 -specific CD8 ؉ T cells by genetic vaccination and show their high protective effect against FV challenge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…GagL 85-93 -specific CD8 ؉ T cells are efficiently induced by DNA immunization with a plasmid encoding the native leader-Gag sequence. In previous work, we were surprised to find that the native leader-Gag sequence did not induce any GagL 85-93 -specific CD8 ϩ T cell responses in mice if it was delivered by an Ad-based vector (20); this was an unexpected finding because of the apparent immunodominance of the GagL 85-93 epitope in the native FV infection. We hypothesized that either other FV-derived proteins, such as F-MuLV protease, may be necessary for efficient processing of the GagL 85-93 epitope or the GagL 85-93 -specific response is dominated by Ad-derived T cell epitopes.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…GagL 85-93 -specific CD8 ؉ T cells are efficiently induced by DNA immunization with a plasmid encoding the native leader-Gag sequence. In previous work, we were surprised to find that the native leader-Gag sequence did not induce any GagL 85-93 -specific CD8 ϩ T cell responses in mice if it was delivered by an Ad-based vector (20); this was an unexpected finding because of the apparent immunodominance of the GagL 85-93 epitope in the native FV infection. We hypothesized that either other FV-derived proteins, such as F-MuLV protease, may be necessary for efficient processing of the GagL 85-93 epitope or the GagL 85-93 -specific response is dominated by Ad-derived T cell epitopes.…”
Section: Resultsmentioning
confidence: 91%
“…However, once the leader-Gag protein is placed in an environment conditioned by a viral vector, the GagL 85-93 epitope seems to lose its dominance. Our work with Ad-based vectors (20) and with the epitope strings presented here clearly demonstrates an impaired induction of GagL 85-93 -specific CD8 ϩ T cells in the presence of Ad-derived epitopes, and results from earlier studies using vaccinia virus-based vectors to deliver leader-Gag indicate a similar situation (32); while those authors did not analyze the CD8 ϩ T cell response to the GagL 85-93 epitope directly, which was described only some years later (15), their experiments indicated that the matrix protein contained the most protective determinant, not the Gag-leader, suggesting that GagL 85-93 -specific CD8 ϩ T cells were not induced by the vaccinia virus-based vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epitope enhancement by sequence modification was designed to improve such vaccines by increasing the immunogenicity of cancer epitopes that are often derived from self antigens [3], [6][8], [34], [35]. Despite occasional findings that some modified peptides may not always be recognized by tumor-reactive T cells [36], sequence modifications both within the epitope and in flanking residues have been useful in increasing immunogenicity in many cases, by affecting MHC binding or antigen processing [3], [7], [23], [37], [38]. For these reasons, we have undertaken identification and epitope enhancement of epitopes from the novel tumor antigen POTE presented by the most common human HLA class I molecule, HLA-A2 (HLA-A*0201).…”
Section: Discussionmentioning
confidence: 99%